Arterial switch for double-outlet left ventricle – Diagnostic and surgical considerations - Ganapathy Krishnan Subramaniam; Pradeep Gnanasekaran; Dhruva Sharma; Rajesh Kumar; Anitha Chandrashekhar (Annals of Pediatric Cardiology, 2022)
Double-outlet left ventricle (DOLV) is a rare congenital cardiac anomaly in which both the aorta and pulmonary artery arise completely or predominantly from the left ventricle. DOLV is a spectrum and can be classified depending on the position of the ventricular septal defect (VSD) relative to the great vessels, the relationship of the great vessels, and the presence or absence of pulmonary or aortic outflow obstruction. In the absence of tricuspid atresia or hypoplastic right ventricle, two ventricle repair is the preferred surgical treatment. We report a 31-day-old, 2.1 kg neonate with DOLV, subaortic VSD who underwent a successful arterial switch with VSD closure.